2016
DOI: 10.1097/brs.0000000000001459
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Adjacent Cranial Facet Joint Violation Following Pedicle Screw Insertion Using Cortical Bone Trajectory Technique

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
3
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 20 publications
3
68
3
5
Order By: Relevance
“…5 Santoni et al 5 proposed a shorter and slimmer screw design whose specific trajectory allowed maximization of contact with the cortical bone. It has been demonstrated that CBT exerts a lower likelihood of violating the facet joint 6 , and superior pull-out strength than the TT screws, especially in osteoporotic vertebral body. [5][6][7][8][9] Additionally, due to its diverging trajectory, CBT results in minimal surgical wound and multifidus muscle destruction.…”
Section: Introductionmentioning
confidence: 99%
“…5 Santoni et al 5 proposed a shorter and slimmer screw design whose specific trajectory allowed maximization of contact with the cortical bone. It has been demonstrated that CBT exerts a lower likelihood of violating the facet joint 6 , and superior pull-out strength than the TT screws, especially in osteoporotic vertebral body. [5][6][7][8][9] Additionally, due to its diverging trajectory, CBT results in minimal surgical wound and multifidus muscle destruction.…”
Section: Introductionmentioning
confidence: 99%
“…These points correspond to a 5 or 7 o'clock orientation in the pedicle. Since the spur formation and hypertrophy of the cranial facet joint can overhang to the pars interarticularis in cases with severe facet degeneration, selection of lower entry point, as much as possible, is desirable to avoid damage to the adjacent mobile segment 11) . Following this, the screw paths are made under true lateral fluoroscopic guidance to be directed 25-30°cranially along the inferior border of the pedicle toward the posterior third to posterior half of the superior endplate, using the burr and a straight probe (Fig.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…7). The starting point is at the laminar slope as it inclines cranially; thus, surgeons should prevent slippage toward the cranial side during the procedure, which may induce unintentional cranial facet joint violation by the screws 11) . Because the starting points are located around the medial border of the pedicle, a lateral angle of 10°is sufficient to avoid the risk of central neural injury.…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 2 more Smart Citations